Evidence for protracted fluid mobility from 40Ar/39Ar stepwise crushing of quartz-rich veins and high-grade rocks - Intan Chalid; Jan R. Wijbrans; Yang Wu; Simona Ferrando; Sander Hoogendoorn; Leo M. Kriegsman; Klaudia F. Kuiper (Geochimica et Cosmochimica Acta, 2025)

Seed banking of mediterranean coastal plants: an analysis to identify current seed availability and gaps to guide future seed collection and habitat restoration activities - Marcello De Vitis; Valter Di Cecco; Mohamed Abdelaal; Gianluigi Bacchetta; Jože Bavcon; Kenza Saadiya Benmenni; Maurizio Bianchelli; Magda Bou Dagher Kharrat; Joseph A. Buhagiar; Francesca Carruggio; Angelino Carta; Simona Casavecchia; et al. (Journal of Coastal Conservation, 2025)

Optimization of Transcription Factor-Driven Neuronal Differentiation from Human Induced Pluripotent Stem Cells for Disease Modelling and Drug Screening - Martina Servetti; Martino Caramia; Giulia Parodi; Fabrizio Loiacono; Ennio Nano; Giorgia Biddau; Lorenzo Ferrando; Lisastella Morinelli; Pierluigi Valente; Sergio Martinoia; Andrea Escelsior; Gianluca Serafini; et al. (Stem Cell Reviews and Reports, 2025)
Progress of human brain in vitro models stands as a keystone in neurological and psychiatric research, addressing the limitations posed by species-specific differences in animal models. The generation of human neurons from induced pluripotent stem cells (iPSCs) using transcription factor reprogramming protocols has been shown to reduce heterogeneity and improve consistency across different stem cell lines. Despite notable advancements, the current protocols still exhibit several shortcomings. This study focuses on standardizing and optimizing the procedure for iPSC-derived glutamatergic neurons generation through the inducible overexpression of Neurogenin-2. Noteworthy refinements include stringent scrutiny of genomic rearrangements post-fibroblast reprogramming, selection of a homogeneously integrated NGN2-cassettes population, and the incorporation of an intermediate step during neuronal differentiation to store neuronal progenitors. The neural culture showed a high degree of neuronal maturation and consistency, as shown by single-cell and network electrophysiological recordings. These advancements aim to provide more reliable tools for disease modelling and drug screening in neurological disorders. Graphical Abstract

New insights from plumbing system below composite mafic volcanoes: Post-glacial volatile contents and magmatic fluids from Villarrica magmas - Philippe Robidoux; Yves Moussallam; Estelle F. Rose-Koga; Andrea Luca Rizzo; Guillaume Georgeais; Joao Lages; Gilles Lévresse; Simona Ferrando; Alessandro Aiuppa (Lithos, 2024)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Late-Alpine rodingitization in the Bellecombe meta-ophiolites (Aosta Valley, Italian Western Alps): evidence from mineral assemblages and serpentinization-derived H 2 -bearing brine - Simona Ferrando; Maria Luce Frezzotti; Paolo Orione; Riccardo Carlo Conte; Roberto Compagnoni (International Geology Review, 2010)